Impact of workspace environment on creativity and innovation: empirical evidence from a makerspace in China - Huang, Y.; Ferreira, F.; Zheng, H. (R e D Management, 2023)
Among the various factors affecting creativity and innovation, workspace environment has not been fully considered by most organizations. The literature on innovation shows that few empirical studies have investigated the influence of workspace environment on creativity and innovation. Using Ucommune (i.e., one of the largest makerspaces and entrepreneurial ecosystems in China) as an example, this research explored to what extent workspace environments affect individual and team creativity and innovation in organizations. The main results include that physical and non-physical environments contribute positively to employees’ individual and team behaviors. In addition, individual behavior can help improve employee creativity and enhance team behavior, but the direct impact of individual behavior on innovation is insignificant. Finally, team behavior can enhance organizational innovation. The findings thus provide empirical support for the increasing importance of the impact of workspace environments – especially their physical aspects – on creativity and innovation.